Influence of blood metabolites and metabolic hormones on response and conception in postpartum Sahiwal cows after Ovsynch treatment* - ALI, SARFRAJ; AWASTHI, M K; KHAN, J R; TIWARI, R P (The Indian Journal of Animal Sciences, 2011)
Present investigation was conducted to investigate the influence of blood metabolites and metabolic hormones on conception after Ovsynch treatment in postpartum Sahiwal cows. Experimental animals (12) were randomly divided in to 2 groups, of 6 animals each. Animals of group 1 were treated with traditional Ovsynch protocol beginning on day 60 postpartum (day 0 of Ovsynch protocol), while animals of group 2 were treated with a modified Ovsynch protocol, where first GnRH injection was replaced with hCG. Treated animals were inseminated at fixed time between 14 and 20 h after second GnRH injection without estrus detection. Blood samples were collected from each experimental animal on days 50, 60 and 68 postpartum; and blood glucose and serum concentrations of non-esterified fatty acid (NEFA), insulin, tri iodothyronine (T3), thyroxin (T4) and progesterone (P4) were determined. Non-conceived animals recorded significantly higher mean serum NEFA concentration than in conceived animals on days 50, 60 and 68 postpartum. Conceived animals had significantly higher blood glucose concentration on day 68, significantly higher serum insulin concentration on days 50, 60 and 68, significantly higher serum T3 concentration on days 60 and 68 and significantly higher serum T4 concentration on day 60 postpartum than in non-conceived animals. From the present study, it may be concluded that decreased serum NEFA concentration and an increased level of blood glucose and serum concentrations of insulin, T3 and T4 probably favoured to achieve conception in Ovsynch treated postpartum Sahiwal cows.